Polyurethane-based solid-solid phase change temperature adjusting material for summer asphalt pavement suitable for multiple climate regions and preparation method of polyurethane-based solid-solid phase change temperature adjusting material

By rationally configuring polyethylene glycol, isocyanate and curing agent in polyurethane-based solid-solid phase change materials, the problem of unreasonable leakage and phase change temperature on asphalt pavement is solved, and the effect of no leakage and reasonable temperature adjustment in high temperature environments is achieved. It is suitable for summer asphalt pavement in multi-climate areas.

CN119955060AActive Publication Date: 2025-05-09SHANDONG UNIV OF SCI & TECH

Patent Information

Application Number
CN202510438049.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-09
Publication Date
2025-05-09
Estimated Expiration
2045-04-09

AI Technical Summary

Technical Problem

Traditional solid-liquid phase change materials are prone to leakage problems during use of asphalt pavement, and their phase change temperature and crystallization temperature are not within reasonable ranges, making it difficult to meet the temperature adjustment requirements of asphalt pavement in summer.

Method used

Polyurethane-based solid-solid phase change material (PUSSPCM) is used to reasonably configure polyethylene glycol (PEG), isocyanate and curing agent to control the phase change temperature of the material between 37 and 54℃, and remain completely solid and leak-free at 190℃.

Benefits of technology

It realizes leakage resistance without leakage in the high-temperature construction environment of asphalt pavement, and regulates the phase change temperature in a reasonable range to meet the temperature adjustment needs of asphalt pavement in summer and is suitable for multi-climatic areas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119955060A_ABST
    Figure CN119955060A_ABST
Patent Text Reader

Abstract

The invention provides a polyurethane-based solid-solid phase change temperature adjusting material for a summer asphalt pavement suitable for multiple climate regions and a preparation method thereof, the reaction raw materials comprise polyethylene glycol, isocyanate and a curing agent, the molecular weight of the polyethylene glycol is 10000 and / or 20000; the molar ratio of isocyanate to polyethylene glycol is (10-20): 1; the molar ratio of the curing agent to the isocyanate is 1: (6-12); the phase-change temperature of the obtained polyurethane-based solid-solid phase-change temperature-adjusting material is 37-54 DEG C, and the polyurethane-based solid-solid phase-change temperature-adjusting material is kept in a completely solid state and leakage-free state at 190 DEG C. The phase change temperature range of the PUSSPCM material is suitable for summer asphalt pavements in different climate areas, good leakage resistance can still be kept in the high-temperature construction environment of the asphalt pavements, it can be ensured that the PUSSPCM material is free of leakage in the application process of the asphalt pavements, and meanwhile the PUSSPCM material can be suitable for effective temperature adjustment of the southern and northern asphalt pavements in China in summer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of phase change temperature regulating materials, and specifically relates to a polyurethane-based solid-solid phase change temperature regulating material for summer asphalt pavement applicable to multiple climate zones and a preparation method thereof. Background Art

[0002] Black asphalt pavement has a high absorption rate of solar radiation, causing the pavement temperature to reach over 60ºC in summer. High pavement temperature not only induces high-temperature pavement diseases such as rutting, puddling and oiling, shortening the pavement service life, but also promotes the release of components such as alkanes, nitrogen hydrocarbons, and sulfur hydrocarbons in asphalt into the atmosphere, causing acid rain, haze and other problems. In addition, high pavement temperature also increases building energy consumption in urban areas and reduces urban travel comfort. In view of the significant adverse effects of high-temperature asphalt pavement environment in summer on the pavement's own service life and the environment, it is extremely necessary to take effective measures to regulate the temperature of asphalt pavement in summer.

[0003] Phase change heat storage technology is an effective active temperature control technology and has become a hot area in the research of self-temperature regulating asphalt pavement in recent years. However, traditional solid-liquid phase change materials not only significantly reduce the road performance of asphalt pavement, but also gradually lose the temperature control effect on the pavement due to leakage problems. Therefore, the leakage resistance design of solid-liquid phase change materials is a key technology.

[0004] At present, relevant research mainly focuses on the physical encapsulation of solid-liquid phase change materials, but it cannot solve the leakage problem during the use of asphalt pavement. The reason is that the solid-liquid composite phase change material prepared in this way does not change the nature of solid-liquid phase change. The matrix material (such as porous diatomaceous earth, porous graphite, microcapsule wall) is very easy to crack or even damage under the high-speed shear of modified asphalt, the rolling of asphalt mixture construction and the load of asphalt pavement vehicles, which leads to leakage problems.

[0005] In contrast, chemically encapsulated polyurethane-based solid-solid phase change materials (PUSSPCMs) can fundamentally solve the leakage problem in asphalt pavement applications, but have received little attention. PUSSPCMs are usually block copolymers formed by alternating hard segments (isocyanates and curing agents) and soft segments (polyethylene glycol PEG). During the phase change process, the chemical bonds between the hard and soft segments and the hydrogen bonds in the hard segments jointly restrict the macroscopic flow of PEG, and then the PEG undergoes a phase transition from a crystalline solid to an amorphous solid. It should be pointed out that the structure of PUSSPCMs has a significant impact on its phase change temperature, phase change heat storage capacity, and leakage resistance. The high temperature scenario of asphalt pavement in summer puts forward specific requirements for the applicable PUSSPCMs, mainly including: (1) PUSSPCMs should not only have no leakage within the phase change temperature range, but also should have no leakage under the high temperature construction environment of asphalt pavement; (2) The melting temperature and crystallization temperature of PUSSPCMs should be within a reasonable range to ensure that PUSSPCMs can play a phase change heat absorption function during the high temperature period during the day in summer, and then release the absorbed heat in time at night.

[0006] The leakage resistance of phase change materials determines its applicability in asphalt pavement temperature control. Solid-liquid composite phase change materials inevitably have leakage risks in asphalt pavements, while polyurethane-based solid-solid phase change materials (PUSSPCM) can fundamentally avoid leakage problems. Among them, it is necessary to focus on solving the leakage resistance of PUSSPCM in the high-temperature construction environment of asphalt pavements. At present, no other reports other than the inventor have paid attention to it. For this reason, solving the leakage resistance of PUSSPCM in the high-temperature construction environment of asphalt pavements through reasonable configuration is the first technical problem to be solved by the patent of this invention.

[0007] The structure of PUSSPCM has a significant impact on its phase change temperature, phase change heat storage capacity, leakage resistance and other properties. Therefore, on the basis of solving the first technical problem, it is also necessary to control the phase change temperature of PUSSPCM within a reasonable range. Current related research focuses on the melting temperature and ignores the crystallization temperature, which causes the crystallization temperature of PUSSPCM to be often too low and difficult to meet the use requirements. In view of this, through reasonable configuration, regulating the phase change temperature of PUSSPCM within a reasonable range is the second technical problem to be solved by the patent of this invention.

[0008] The application number is 201310739247.0, and the patent name is "A method for preparing linear polyurethane phase change energy storage material". Although the patent discloses the phase change temperature of the material and focuses on the melting temperature and crystallization temperature performance of the material, the material is applied to asphalt pavement and the leakage resistance of the material is not ideal under high-temperature construction environment.

[0009] The application number is 201810025916.0, and the patent name is a polyethylene glycol / hydroxypropyl methylcellulose solid-solid phase change material and its preparation method. Although the patent focuses on the leakage problem, it only focuses on its anti-leakage performance within the phase change temperature range, and does not consider the anti-leakage performance at temperatures of 185°C and above. When applied to asphalt pavement and in high-temperature construction environments, the material's anti-leakage performance is not ideal, and the melting temperature and crystallization temperature of the material are not in a reasonable range, making it difficult to meet the use requirements. Summary of the invention

[0010] In order to solve the above problems, the present application proposes a polyurethane-based solid-solid phase-change temperature-adjusting material for summer asphalt pavement applicable to multiple climate zones, wherein the reaction raw materials include polyethylene glycol (PEG), isocyanate, and curing agent; The molecular weight of polyethylene glycol is 10,000 and / or 20,000; The molar ratio of isocyanate to polyethylene glycol is (10-20):1; The molar ratio of curing agent to isocyanate is 1:(6-12); The phase change temperature of the obtained polyurethane-based solid-solid phase change temperature regulating material is set at 37-54°C and it maintains a completely solid and leak-free state within 190°C.

[0011] The phase change temperature in this application is explained as: melting temperature ≤ 54°C, crystallization temperature ≥ 37°C, and the phase change temperature of the material is 37~54°C.

[0012] Furthermore, the molecular weight of polyethylene glycol in the reaction raw material is 10000, the molar ratio of isocyanate to polyethylene glycol is (10-12):1, and the phase change temperature of the obtained polyurethane-based solid-solid phase change temperature regulating material is set at 37~49°C and remains in a completely solid and leak-free state within 190°C.

[0013] Furthermore, the molecular weight of polyethylene glycol in the reaction raw material is 20,000, the molar ratio of isocyanate to polyethylene glycol is (10-20):1, and the phase change temperature of the obtained polyurethane-based solid-solid phase change temperature regulating material is set at 42-54°C and remains in a completely solid, leak-free state within 190°C.

[0014] Furthermore, the molecular weights of polyethylene glycol are 10,000 and 20,000, the compounding molar ratio of polyethylene glycol with a molecular weight of 10,000 and polyethylene glycol with a molecular weight of 20,000 is (0.1-5):1, the molar ratio of isocyanate to polyethylene glycol is (10-20):1, and the phase change temperature of the obtained polyurethane-based solid-solid phase change temperature regulating material is 41-51°C and remains in a completely solid, leakage-free state within 190°C.

[0015] Furthermore, the isocyanate is diphenylmethane diisocyanate (MDI); the curing agent is one or more of 3,3'-dichloro-4,4'-diphenylmethanediamine (MOCA), 3,5-dimethylthiotoluenediamine (DMTDA), and 3,5-diethyltoluenediamine (DETDA).

[0016] Preferably, the molar ratio of curing agent to MDI is 1:(8-10).

[0017] The present application also provides a method for preparing a polyurethane-based solid-solid phase change temperature regulating material for summer asphalt pavement suitable for multiple climate zones, the steps of which are as follows: adding polyethylene glycol to a solvent and dissolving it to obtain a polyethylene glycol solution; under a nitrogen protection atmosphere, adding MDI to the polyethylene glycol solution and mixing and reacting for 5 to 120 minutes, then adding a curing agent and waiting for 5 to 180 minutes, and then placing the mixture in a vacuum environment to remove the solvent to obtain a polyurethane-based solid-solid phase change temperature regulating material.

[0018] Further, the solvent is one or more of N,N-dimethylformamide (DMF), dichloromethane (DCM), tetrahydrofuran (THF), and toluene; The mass ratio of solvent to polyethylene glycol is (5-10):1.

[0019] Furthermore, the reaction temperature is 75-85°C.

[0020] Preferably, the reaction temperature is 80°C.

[0021] The present application also provides another method for preparing a polyurethane-based solid-solid phase change temperature regulating material for summer asphalt pavement suitable for multiple climate zones, the steps of which are as follows: preparation by bulk polymerization method, the steps of which are: adding polyethylene glycol and MDI, stirring and reacting at 75-85°C under nitrogen protection for 5-120 minutes, then adding a curing agent and continuing to stir and react for 5-180 minutes to obtain a polyurethane-based solid-solid phase change temperature regulating material.

[0022] The present application provides a specific application scenario of the material, applying the polyurethane-based solid-solid phase change temperature regulating material to asphalt pavement, and adding the polyurethane-based solid-solid phase change temperature regulating material to a hot mix asphalt mixture to maintain a completely solid and leakage-free state.

[0023] The polyurethane-based solid-solid phase-change temperature regulating material prepared in the present application can give full play to its material advantages, especially when used on asphalt pavement in summer, and can be used in multiple climate zones.

[0024] Based on the measured data of temperature changes of asphalt pavements in summer in northern and southern my country, this application proposes a reasonable PUSSPCM phase change temperature range. The PUSSPCM designed accordingly can meet the temperature control needs of asphalt pavements in northern and southern my country in summer.

[0025] This application can bring the following beneficial effects: The phase change temperature range of the PUSSPCM material designed by the patent of the present invention is suitable for use in asphalt pavements in summer in different climate zones, and can still maintain good leakage resistance under the high-temperature construction environment of asphalt pavements. The PUSSPCM can not only ensure that there is no leakage problem during the application of asphalt pavements, but also can be used for effective temperature control of asphalt pavements in the north and south of my country in summer. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings: Figure 1 These are the results of measuring the temperature changes of the local asphalt pavement surface layer in summer.

[0027] Figure 2 Leakage resistance test results.

[0028] Figure 3 This is a picture of limited mobility during the synthesis process. DETAILED DESCRIPTION

[0029] Unless otherwise specified, the reagents and instruments used in the following examples are commercially available products.

[0030] The preparation method of the polyurethane-based solid-solid phase change thermostatic material of the present application can use conventional synthesis methods. The present application lists the following two preparation methods: Method 1: Solution polymerization The steps are: adding polyethylene glycol to a solvent to dissolve it to obtain a polyethylene glycol solution; under a nitrogen protection atmosphere, adding MDI to the polyethylene glycol solution and mixing them to perform a prepolymer reaction; then adding a curing agent to perform a curing reaction, placing the mixture in a vacuum environment to remove the solvent, and obtaining a polyurethane-based solid-solid phase change temperature control material.

[0031] Method 2: Bulk polymerization, that is, directly mixing the raw materials without the need for a solution The steps are: adding polyethylene glycol and MDI, stirring under nitrogen protection to carry out prepolymer reaction, and then adding a curing agent to carry out curing reaction to obtain a polyurethane-based solid-solid phase change temperature regulating material.

[0032] In order to demonstrate the technical effect of the present application, the specific implementation is as follows Table 1: Table 1 Specific implementation method Preparation process parameters

[0033]

Characterization

[0034] 2. Leakage resistance test: Place the sample on a filter paper with strong water absorption, and then place it in an environment of 70℃, 135℃ and 190℃ for 2 hours respectively, and observe the water absorption of the filter paper. If the filter paper absorbs water, it means that the material is leaking. If the filter paper does not absorb water, it means that the material is not leaking. The test results are shown in Table 2 and attached. Figure 2 .

[0035] Table 2 Material performance test results

[0036] From the characterization results in Table 2, it can be analyzed that the polyurethane-based solid-solid phase change temperature regulating material obtained in the present application, by controlling the ratio of polyethylene glycol molecular weight, isocyanate, polyethylene glycol and curing agent, has a phase change temperature of 37~54°C and maintains a completely solid and leak-free state within 190°C.

[0037] In Example 1-2 of the present invention, polyethylene glycol with a molecular weight of 10,000 is used alone, and the molar ratio of isocyanate to polyethylene glycol is controlled at (10-12):1. The phase change temperature of the obtained polyurethane-based solid-solid phase change temperature regulating material is set at 37-49°C and remains in a completely solid, leak-free state within 190°C.

[0038] In Example 3-8 of the present invention, polyethylene glycol with a molecular weight of 20,000 is used alone, and the molar ratio of isocyanate to polyethylene glycol is controlled at (10-20):1. The phase change temperature of the obtained polyurethane-based solid-solid phase change temperature regulating material is set at 42-54°C and remains in a completely solid, leak-free state within 190°C.

[0039] The present invention also provides two technical solutions for molecular weight compounding. For example, in Examples 9-11, the compounding molar ratio of polyethylene glycol with a molecular weight of 10,000 and polyethylene glycol with a molecular weight of 20,000 is (0.1-5):1, and the molar ratio of isocyanate to polyethylene glycol is controlled at (10-20):1. The phase change temperature of the obtained polyurethane-based solid-solid phase change temperature regulating material is 41-51°C and remains in a completely solid, leakage-free state within 190°C.

[0040] The melting temperature represents the starting temperature at which the material changes from an ordered solid state to a disordered solid state. When the ambient temperature rises to the melting temperature, the material absorbs heat to slow down the temperature rise of the asphalt pavement and reduce the risk of rutting under high temperatures in summer. By absorbing heat, it prevents the viscosity of asphalt from dropping suddenly and improves its anti-rutting ability.

[0041] The crystallization temperature represents the starting temperature at which the material recovers from a high-temperature disordered solid state to a low-temperature ordered solid state. When the ambient temperature drops to the crystallization temperature, the material releases the stored heat, delaying the sudden drop in road surface temperature and reducing the risk of low-temperature cracking in winter.

[0042] Melting temperature and crystallization temperature are the core parameters for polyurethane solid-solid phase change materials to achieve temperature regulation on asphalt pavement. The smaller the difference (hysteresis width) between melting and crystallization temperatures, the more beneficial it is to energy utilization efficiency. The material obtained by the present invention has a smaller hysteresis width, which can improve energy utilization efficiency.

[0043] The greater the melting enthalpy, the more heat the material absorbs when the temperature rises, and the more significant the cooling effect on the environment; the greater the crystallization enthalpy, the more heat the material releases when the temperature drops, and the stronger the heat preservation effect on the environment. The present invention significantly improves the melting enthalpy and crystallization enthalpy of the material obtained by compounding PEG10000 and PEG20000, such as Examples 9-11.

[0044] On the one hand, the increase in the hard segment content in PUSSPCM can effectively enhance the restriction on the thermal motion of the PEG chain segments, allowing the material to remain in a stable solid state at higher temperatures, thereby significantly improving the anti-leakage performance.

[0045] On the other hand, the increase in the hard segment content will also inhibit the crystallization behavior of PEG, resulting in a decrease in the temperature required for PEG crystallization, that is, the overall crystallization temperature of the material is lowered. At this time, if a low molecular weight PEG is selected, such as Comparative Example 2-3, its own crystallization temperature is low, and after the inhibitory effect of the hard segment is added, the crystallization temperature of PUSSPCM will be reduced to a temperature range that is difficult to meet the use temperature required for summer asphalt pavement.

[0046] In contrast, high molecular weight PEG has a higher initial crystallization temperature and longer chain segments, which helps to retain appropriate crystallization ability while being inhibited by the hard segment, so that the material can maintain a reasonable crystallization temperature while maintaining leakage resistance. Only when the PEG molecular weight is increased to 10,000 or above, can PUSSPCM achieve an effective balance between crystallization temperature and leakage resistance, meeting the dual needs of thermal energy storage and practical applications.

[0047] When the molar ratio of isocyanate to polyethylene glycol is too low, such as shown in Comparative Examples 4-5 and Comparative Examples 7-8, the isocyanate content is difficult to effectively limit the thermal motion of the PEG molecular chain at 190°C, and the PUSSPCM has a leakage problem. When the molar ratio of isocyanate to polyethylene glycol is too high, such as shown in Comparative Examples 6 and 9, the viscosity of the system increases too fast, and the problem of limited fluidity occurs (such as the attached Figure 3 When MDI is in excess, the solution gradually thickens during the reaction between MDI and PEG, resulting in limited fluidity (the "climbing pole" effect), which makes the synthesis process unable to continue.

[0048] When the PEG molecular weight is too low, the sample cannot be successfully synthesized due to fluidity problems, such as shown in Comparative Example 1.

[0049] The curing agent and isocyanate jointly play a limiting role on the PEG molecular chain. When the curing agent content is too low, as shown in Comparative Example 10, the synthetic PUSSPCM leakage resistance does not meet the requirements. At the same time, when the curing agent content is too low, the short molecular chains of the prepolymer cannot be fully connected to form macromolecules, resulting in poor mechanical properties. When the curing agent content is too high, as shown in Comparative Example 11, the system viscosity will also increase too quickly, resulting in the inability to continue the synthesis process.

[0050]

Material application display

[0051] From the attached Figure 1 It can be analyzed that the road surface temperature is always higher than the atmospheric temperature, and the daytime temperature of the surface layer is higher than 54°C, and the highest temperature can reach nearly 60°C, which is closely related to the high absorption of solar radiation by black asphalt pavement. The daytime temperature decreases significantly with the decrease of the layer position, while the nighttime temperature shows the opposite trend, but the influence of the layer position on the nighttime temperature is not obvious, and the lowest temperature is mainly concentrated in the range of 30-35°C. In addition, due to the climate differences between Shandong and Guangdong, the daytime temperature of asphalt pavement is also different. Therefore, the phase change temperature of phase change heat storage asphalt pavement material should be controlled between 35-60°C.

[0052] The phase transition temperature of PUSSPCM obtained in the present invention is in the range of 37-54°C (melting temperature ≤54°C, crystallization temperature ≥37°C), so the PUSSPCM prepared by the present invention can fully meet the temperature control needs of asphalt pavements in summer in northern and southern my country.

[0053] In addition, the construction temperature of hot-mix asphalt mixture in my country is usually between 160 and 185 degrees Celsius. However, the PUSSPCM of the present invention still maintains good anti-leakage performance at 190 degrees Celsius, which is fully capable of achieving no leakage during the construction of hot-mix asphalt mixture in my country.

[0054] Each embodiment in this specification is described in a progressive manner, and the same or similar parts between the embodiments can be referred to each other, and each embodiment focuses on the differences from other embodiments. In particular, for the system embodiment, since it is basically similar to the method embodiment, the description is relatively simple, and the relevant parts can be referred to the partial description of the method embodiment.

[0055] The above is only an embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application should be included in the scope of the claims of the present application.

Claims

1. A polyurethane-based solid-solid phase-change temperature regulating material for summer asphalt pavement suitable for multiple climate zones, characterized by: The reaction raw materials include polyethylene glycol, isocyanate, and curing agent; The molecular weight of polyethylene glycol is 10,000 and / or 20,000; The molar ratio of isocyanate to polyethylene glycol is (10-20):1; The molar ratio of curing agent to isocyanate is 1:(6-12); The obtained polyurethane-based solid-solid phase change temperature regulating material has a phase change temperature of 37-54°C and maintains a completely solid and leak-free state within 190°C.

2. The polyurethane-based solid-solid phase-change temperature regulating material for asphalt pavement in summer applicable to multiple climate zones according to claim 1, characterized in that: The molecular weight of polyethylene glycol is 10000, the molar ratio of isocyanate to polyethylene glycol is (10-12):1, and the phase change temperature of the obtained polyurethane-based solid-solid phase change temperature regulating material is 37-49°C and it maintains a completely solid and leak-free state within 190°C.

3. The polyurethane-based solid-solid phase-change temperature regulating material for asphalt pavement in summer applicable to multiple climate zones according to claim 1, characterized in that: The molecular weight of polyethylene glycol is 20000, the molar ratio of isocyanate to polyethylene glycol is (10-20):1, and the phase change temperature of the obtained polyurethane-based solid-solid phase change temperature regulating material is 42-54°C and it maintains a completely solid and leak-free state within 190°C.

4. The polyurethane-based solid-solid phase-change temperature regulating material for asphalt pavement in summer applicable to multiple climate zones according to claim 1, characterized in that: The molecular weights of polyethylene glycol are 10,000 and 20,000, the molar ratio of polyethylene glycol with a molecular weight of 10,000 to polyethylene glycol with a molecular weight of 20,000 is (0.1-5):1, the molar ratio of isocyanate to polyethylene glycol is (10-20):1, and the phase change temperature of the obtained polyurethane-based solid-solid phase change temperature regulating material is 41-51°C and remains in a completely solid, leak-free state within 190°C.

5. The polyurethane-based solid-solid phase-change temperature regulating material for asphalt pavement in summer applicable to multiple climate zones according to claim 1, characterized in that: The isocyanate is MDI; the curing agent is one or more of 3,3'-dichloro-4,4'-diphenylmethanediamine, 3,5-dimethylthiotoluenediamine, and 3,5-diethyltoluenediamine; and the molar ratio of the curing agent to MDI is 1:(8-10).

6. The method for preparing the polyurethane-based solid-solid phase change temperature regulating material according to any one of claims 1 to 5, characterized in that: Adding polyethylene glycol into a solvent and dissolving it to obtain a polyethylene glycol solution; Under a nitrogen protective atmosphere, MDI is added to the polyethylene glycol solution and mixed for reaction for 5 to 120 minutes. Then, a curing agent is added and waited for 5 to 180 minutes. The mixture is placed in a vacuum environment to remove the solvent to obtain a polyurethane-based solid-solid phase change temperature control material.

7. The preparation method according to claim 6, characterized in that: The solvent is one or more of N,N-dimethylformamide, dichloromethane, tetrahydrofuran, and toluene; The mass ratio of solvent to polyethylene glycol is (5-10):

1.

8. The preparation method according to claim 6, characterized in that: The reaction temperature is 75-85°C.

9. The method for preparing the polyurethane-based solid-solid phase change temperature regulating material according to any one of claims 1 to 5, characterized in that: The bulk polymerization method is used for preparation, and the steps are: adding polyethylene glycol and MDI, stirring and reacting at 75-85°C for 5-120 minutes under nitrogen protection, and then adding a curing agent and continuing to stir and react for 5-180 minutes to obtain a polyurethane-based solid-solid phase change temperature regulating material.

10. The polyurethane-based solid-solid phase change temperature regulating material according to any one of claims 1 to 5 or the polyurethane-based solid-solid phase change temperature regulating material prepared by the preparation method according to any one of claims 6 to 9, characterized in that: The polyurethane-based solid-solid phase change temperature regulating material is applied to asphalt pavement, and the polyurethane-based solid-solid phase change temperature regulating material is added to the hot mix asphalt mixture to maintain a completely solid and leakage-free state.

Citation Information

Patent Citations

  • A method for preparing a linear polyurethane phase change energy storage material

    CN103739812B

  • Polyethylene glycol / hydroxypropyl methyl cellulose solid-solid phase change material and preparation method thereof

    CN108276544A

  • Preparation method of paraffin / polyurethane solid-solid composite double-phase change energy storage material

    CN103224601A

  • Preparation method for hyperbranched polyurethane-modified asphalt with temperature sensibility controllable

    CN105885440A

  • Polyurethane / carbon black composite solid-solid phase change material-modified asphalt mixture and preparation method thereof

    CN108751801A

Cited By

  • High-performance PUSSPCM phase-change self-temperature-regulating asphalt suitable for summer pavement and preparation method of PUSSPCM phase-change self-temperature-regulating asphalt

    CN121610091A

  • High-performance PUSS PCM phase change self-temperature-regulating asphalt suitable for summer roads and a preparation method thereof

    CN121610091B